Reproduction of Macrobrachiummammilodactylus from swamp area around the Riau Main Stadium, Pekanbaru - Litavia, Widya; Windarti, Windarti; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Macrobrachiummammilodactyluswas a type of freshwater shrimp that inhabits swamp area around the Riau Main Stadium. The population of shrimp in the swamp was relatively high and it indicatesthat the reproduction of the shrimp was succeed.This research aims to understandthe reproductive biological aspectsof the shrimp and it was conducted in March-April 2018.Sampling were conducted 4 times, once/week.Totally 100 shrimps (20 males and 80 females) were caught, 26.71-44.67mm TL and 0.2052-0.814gr BW.Male and female sex ratio is 1:4. In each sampling time there were shrimps with 2nd, 3rd, 4th maturity levels. Gonad Somatic Index (GSI) of the male was ranged from 0.48% -3.56% and the female was ranged from 0.02-9.30%. Fecunditywas around 137-208 eggs / shrimp and the egg diameter was 0.6-0.8 mm.There were 52 ovigerous females that carried 67-218 eggs / female.The diameter of the abdomen’s attached eggs range from 0.6-0.9 mm, and the embryos were in 1st stage (eyeless embryos) and 2nd stage (embryos with developing eyes).In the ovigerous females, there were several individuals that have developing eggs inside their ovary (in the 2nd and 3rd maturity levels).This fact indicates that M. mammilodactylusisa partial spawner. Keyword : Freshwater Shrimp, Sex Ratio, GSI, Maturity Level, ovigerous females